Evaluation of drug promotional literatures on angiotensin receptor blockers using World Health Organization criteria - Bhaumik, Debasree; Das, Lakshman; Bhattacharjee, Prithul; Chakraborty, Maitrayee; Ghosh, Ranjib (Asian Journal of Medical Sciences, 2022)
Background: Drug promotional literatures (DPLs) are one of the well-known promotional activities of pharmaceutical industries which are sometimes inaccurate as well as of poor educational value. Angiotensin receptor blockers (ARBs) are one of the most commonly used antihypertensives. Therefore, this study was done to estimate the accuracy of DPLs on ARBs as per the World Health Organization (WHO) criteria. Aims and Objectives: The aims of this study were to estimate the accuracy of DPLs on ARBs as per the WHO and to estimate the DPLs for types of claims and appropriateness of claims. Materials and Methods: A cross-sectional observational study was carried out for 1 month. All the required information of selected DPLs on ARBs were recorded in a pro forma and were evaluated according to the WHO criteria. Results: In this study, a total of 20 (twenty) DPLs were evaluated only on ARBs. It was observed that none of the DPLs fulfilled all the WHO criteria. In this study, some DPLs made multiple claims, as much as five per DPL. Claims were, further, analyzed and divided into appropriate and inappropriate. We have observed that 65.96% claims were appropriate and 34.04% claims were inappropriate. Conclusion: This type of study can contribute to make prescribing practices rational as promotional activities influence the prescribing behavior of the health-care provider.